Analysis of Science Literacy Skills Among 11th Grade Students on Kinematics Material - Rahmah, Oliv Jumani; Usman, Usman; Wahyuni, A Sri Astika; Setiawan, Trisno (Jurnal Ilmiah Pendidikan Fisika, 2024)
This is survey research aimed at determining the profile of science literacy skills among XI students at State High School 4 Makassar on learning physics in general and based on gender. The population in this study is the entire Class XI of physics students at State High School 4 in Makassar school year 2023/2024 of 3 classes, while the sample of 68 students was selected using purposive sampling. The instruments used in this research to measure the content, knowledge, and competency dimensions were tests, while the attitude dimension was measured using a questionnaire. The data obtained from this research were analyzed using descriptive statistics. The research results showed that the literacy of the scientists in the context and knowledge dimensions was in the middle category, the competence dimensions were in the lower category, and the attitude dimensions were in the high category. When reviewed from a gender perspective, the average literacy score of female students is superior in context implications, while male students are superior in knowledge, competence, and attitude.